Autoimmunity in inflammatory bowel disease: a case of ulcerative colitis with diabetes mellitus, autoimmune hepatitis and autoimmune hypothyroidism - Najafi, Mehri; Zamani, Mohammad Mahdi; Rezaei, Nima; Sabbaghian, Mozhgan (The Turkish Journal of Pediatrics, 2012)
Ulcerative colitis (UC) is a form of inflammatory bowel disease, which occasionally can be associated with autoimmune disorders. Herein, a two-year-old male infant with UC under sulfasalazine therapy is presented, who consequently developed type I diabetes mellitus, autoimmune hepatitis and autoimmune hypothyroidism. Although presence of concurrent autoimmune diseases with UC is a rare condition, it could highlight the role of immune-related mechanisms as a pathogenesis of disease.